Peptide T7-modified polypeptide with disulfide bonds for targeted delivery of plasmid DNA for gene therapy of prostate cancer - Lu Y (Dove Medical Press, 2018)
Yue Lu,1 Wenjun Jiang,1 Xin Wu,2 Saixu Huang,1 Zhiyong Huang,1 Yamin Shi,3 Qi Dai,1 Jianming Chen,2 Fuzheng Ren,1 Shen Gao4 1Shanghai Key Lab New Drug Design, School of Pharmacy, East China University of Science and Technology, Shanghai, People’s Republic of China; 2Shanghai Weier Biological Medicine Science and Technology Co. Ltd., Shanghai, People’s Republic of China; 3Department of Pharmacy, Fujian University of Traditional Chinese Medicine, Fuzhou, People’s Republic of China; 4Department of Pharmaceutics, Changhai Hospital, Second Military Medical University, Shanghai, People’s Republic of China Background: Vectors are essential for successful gene delivery. In the present study, a tumor-targeting cationic gene vector, known as the disulfide cross-linked arginine-aspartic acid peptide modified by HAIYPRH (T7) peptide (CRD-PEG-T7), was designed for targeted delivery of plasmid DNA (pDNA) for gene therapy of prostate cancer (PCa). Methods: The structure of CRD-PEG-T7 was determined and the cellular uptake efficacy, gene transfection efficacy, cytotoxicity, and the targeting effect of the CRD-PEG-T7–plasmid DNA complex were examined. Results: The results demonstrated that the CRD-PEG-T7–plasmid DNA complex was nanosized and had a positively charged surface, good cellular uptake efficacy, minimal cytotoxicity, and a dual-targeting effect as compared with the CRD-PEG–plasmid DNA complex. The peptide T7-modifed new delivery system was able to target the highly expressed transferrin receptor (TfR) on tumor cells with an efficiency four-fold higher than that of the non-modified system. Conclusion: The results above indicatd that the CRD-PEG-T7–plasmid DNA complex may prove to be a promising gene delivery system targeting bone-metastatic tumor. Keywords: arginine peptide, aspartic acid peptide, tumor targeting, DNA delivery, bone metastasis prostate cancer